The indexes of osteogenic stem cells activity in patients with rheumatoid arthritis and frontal knee deformities - Panchenko, Lesya; Avtomeenko, Yevgen; Babko, Andrey; Gerasimenko, Sergey; Gerasimenko, Andrey; Polishko, Vera (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective: to study the indexes of stem cells activity of bone marrow which form knee joint (lateral and medial parts of distal femur and proximal tibia part) which were cut at arthroplasty surgery in patients with rheumatoid arthritis and frontal knee deformity. Methods: spongiest bone was taken at surgery (knee arthroplasty) from medial and lateral sides of distal femur and proximal tibia. Due to cloning method of fibroblast colony forming units we studied in 37 patients with rheumatoid arthritis of knee joint. We studied 168 samples of bone marrow, 204 cultures of stem cells were growth. Results: we observed significant deceleration of reparative process in bone tissue at rheumatoid arthritis. Significant difference of fibroblast colony forming units in 1 sm 3 volume in different parts of knee joint was observed. In the medial femur condylar this index was (0,2307 ± 0,16) · 104, it exceeds values obtained in other areas in 11–20 times. It was shown that stem cells of the lateral tibia condylar had worse conditions for regenerative potential in cases of valgus deformity compare with varus. There were 4 times less amount of fibroblast colony forming units and the efficacy of its cloning was 2.6 times lower. Conclusion: significant differences were revealed in the indexes of osteogenic activity of stem cells which form knee joint (lateral and medial parts of distal femur and proximal tibia part).